Real-time visual feedback about oar force and position helps to adapt rowing technique - Scholtens, E. J.; Lintmeijer, L. L.; van-Soest, A. J.; Hofmijster, M. J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Although previous research indicates the importance of precise and accurate feedback (e.g. Ford et al, 2007), feedback in rowing commonly only consists of verbal input by the coach. In this field study we investigated whether feedback of stroke-related parameters may help a rower improve his technique. According to the coach of the participating crew, its members applied insufficient force on the oar during the final part of the stroke. We investigated whether real-time augmented visual feedback about handle force could help these rowers to postpone the decline of force during the final part of the stroke. Methods: Force on the oar and oar angle were measured using commercial sensor technology (Peach Innovations, UK). Using a custom-made interface, data was streamed in real time to a smartphone, acting both as a data processing unit and a feedback device. The coxless four crew was instructed to row six 3-minute trials while maintaining a high force during the final part of the stroke. In trials 2, 4 and 6 they received feedback about the oar angle at which force dropped below 70% of maximum (provided after each stroke cycle). Dependent variables were the oar angle at which force dropped below 70% of maximum force (angle@70%) and the force on the oar when the oar was at 10 degrees past the orthogonal position (force@10deg). For each trial, 30 consecutive strokes were selected, resulting in a comparison within each rower between 90 strokes in the feedback condition and 90 strokes in the control condition. Results: Due to technical problems, accurate data were obtained for three of the four participants only. These rowers each showed higher values for angle@70% (control: M=17.2, SD=0.656; M=5.87, SD=3.43; M=5.89, SD=1.67, feedback: M=17.3, SD=0.576; M=7.49, SD=2.70; M=6.02, SD=1.91) and force@10deg (control: M=911, SD=47.4; M=642, SD=33.8; M=597, SD=32.7, feedback: M=923, SD=51.2; M=672, SD=31.3; M=601, SD=53.8) during the feedback conditions. On average, force@10deg was 15.3±13.3N higher and angle@70% was 0.617±0.869 degrees higher in the feedback conditions. Discussion: This study suggests that a single training session with augmented real-time feedback may lead to behavioral changes in well-trained rowers. Thus, these results show the potential of real-time augmented feedback in rowing. The combination of a smartphone platform combined with precise sensor technology allows tailoring the type of feedback to the wishes of coach and rower, likely increasing the potential for performance enhancement. In future work, we will investigate to what extent real-time augmented feedback improves rowing performance and whether feedback-induced changes in movement execution are also maintained when feedback is withdrawn.